2016
DOI: 10.1590/1413-81232015219.01602015
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de estratégias educacionais no pré-natal de baixo risco: revisão sistemática de ensaios clínicos randomizados

Abstract: This study aimed to analyze the impact of educational strategies developed in low-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
25
1
17

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 25 publications
1
25
1
17
Order By: Relevance
“…The Ministry of Health of Brazil, through its National Popular Education and Health Policy 11 , and its references, I 12 and II 13 Cadernos de Educação Popular e Saúde 12,13 (Notebooks of Popular Education and Health) recognize educational actions as essential and fundamental strategies for coping with public health issues and health promotion. The systematic review by Silva et al 14 showed the positive impact of participatory educational strategies, such as the use of educational materials during home visits, in facing crucial health issues, generating favorable outcomes such as the reduced rates of prematurity and low birth weight and increased exclusive breastfeeding. A similar outcome was also observed in the study by Santana et al 15 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Ministry of Health of Brazil, through its National Popular Education and Health Policy 11 , and its references, I 12 and II 13 Cadernos de Educação Popular e Saúde 12,13 (Notebooks of Popular Education and Health) recognize educational actions as essential and fundamental strategies for coping with public health issues and health promotion. The systematic review by Silva et al 14 showed the positive impact of participatory educational strategies, such as the use of educational materials during home visits, in facing crucial health issues, generating favorable outcomes such as the reduced rates of prematurity and low birth weight and increased exclusive breastfeeding. A similar outcome was also observed in the study by Santana et al 15 .…”
mentioning
confidence: 99%
“…Many studies and publications focus on to the methodological explanation of the construction and validation of measurement instruments 17,18 as well as the presentation of research geared dedicated to the development and validation of standardized instruments for the evaluation of child development 19 , including those for preterm children. However, few are intended to guide the methodological construction of educational materials, especially those aimed at guiding and empowering the family to promote child development, despite its acknowledged and expressive role in the positive results in children's health, when correctly oriented 2,9,14,15 .…”
mentioning
confidence: 99%
“…5,6 SI begins with a diagnosis of health situation, through recognition of the territory, survey of health problem and / or health system. Subsequently, interventions are developed to try to solve the problems previously raised.…”
mentioning
confidence: 99%
“…5,6,7 The health professional, in this case, the nurse, must be prepared to attend to the pregnant woman in a holistic way and understand all the subjectivity that gestation can cause (physical, nais). Each gestation is unique and each woman will have a distinct experience of this experience.…”
mentioning
confidence: 99%
See 1 more Smart Citation